Chromophobe cell renal carcinoma a case report - Aihara, K (Hinyokika kiyo. Acta urologica Japonica, 2000)
Chromophobe cell renal carcinoma is an uncommon subtype of renal cell carcinoma and the number of cases studied is still limited in Japan. We here report a case of chromophobe cell renal carcinoma in a 41-year-old Mexican male. He visited our branch hospital with the symptom of upper abdominal pain. Ultrasound examination showed a left renal mass. He was admitted to our hospital for treatment of a left renal mass. Radiological examinations revealed a hypervascular tumor in the left kidney. Under the clinical diagnosis of possible renal cell carcinoma, left radical nephrectomy was performed. This tumor was diagnosed as chromophobe cell renal carcinoma with a microscopic examination of H & E stained specimens, histochemical staining using Hale's colloidal iron and an ultrastructural study